Comparison of Polyethylene Glycol 3350 and Lactulose for Treatment of Chronic Constipation in Children - Azam, Zunaira; Zarqoon, Nida; Shafique, Sundas; Fatima, Mehak; Ali, Haris; Gondal, Mudassar Fiaz; Awais, Chaudhary Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Chronic functional constipation (CFC) is a prevalent gastrointestinal disorder characterized by persistent constipation without an identifiable organic cause. The pathophysiology of chronic functional constipation in children involves a complex interaction of behavioral, physiological, and dietary factors. Toilet training is crucial in helping to address functional constipation. The mainstay of pharmacological treatment of chronic functional constipation in adults and the pediatric population includes the use of laxatives. Objective: To compare the efficacy of Polyethylene Glycol 3350 and lactulose in the treatment of chronic constipation in children. Methodology: This study was a quasi-experimental study conducted from September 2024 to March 2025. After obtaining approval from the Ethical Review Board of Rawalpindi Medical University, the sample size of 86 patients was calculated using the Clincalc calculator, with a 95% confidence interval and 80% power, based on statistical literature. Simple non-random consecutive sampling was done. The study sample was divided into two groups, i.e., Group A and Group B. Each group included 43 patients. Patients were divided into two groups by lottery method. Group A included patients receiving PEG 3350, whereas Group B included patients receiving lactulose. Results: Eighty-six patients were selected for the study, fulfilling the sample selection criteria. The mean age of the study population was 5.20 +/-2.39 years. Fifty-three patients were males, i.e., 61.16% of the study population. The post-treatment frequency of stool per week was 3.74 ± 1.13 in group A and 3.30 ± 1.35 in group B, respectively. There was a significant improvement in stool frequency after 2 weeks of treatment in both groups. The treatment success, measured as the percentage of patients achieving success with the treatment in each group, was 72.1% in group A compared to 37.2% in group B. There was a statistically significant difference between the two groups in terms of treatment success, with a p-value of 0.009. Conclusion: The efficacy of Polyethylene Glycol 3350 formulation is significantly greater than that of the lactulose formulation in the treatment of chronic functional constipation in children. The treatment with PEG 3350 is associated with fewer adverse effects compared to lactulose.